2014
DOI: 10.1097/igc.0000000000000015
|View full text |Cite
|
Sign up to set email alerts
|

Bone Metastasis in Primary Endometrial Carcinoma: Features, Outcomes, and Predictors

Abstract: In endometrial carcinoma that develops bone metastasis, isolated bone recurrence and extrapelvic bone metastasis are significant predictors of prolonged survival after the diagnosis of bone metastasis. Further researches on the optimal treatment modality and factors that have the clinical implications are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 15 publications
4
41
0
Order By: Relevance
“…We speculated that the development of diagnostic modalities might have enabled the detection of smaller extra‐osseous lesions. Yoon et al reported that extra‐osseous lesions were associated with a poorer prognosis in patients with bone metastasis from endometrial cancer . In the present study, the same result was observed in cervical cancer.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We speculated that the development of diagnostic modalities might have enabled the detection of smaller extra‐osseous lesions. Yoon et al reported that extra‐osseous lesions were associated with a poorer prognosis in patients with bone metastasis from endometrial cancer . In the present study, the same result was observed in cervical cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Yoon et al reported that the OS of patients with bone metastasis at recurrence was significantly longer than that of patients with bone metastasis at the primary diagnosis in endometrial cancer, but there was no significant difference in survival between recurrence and primary diagnosis in the present cervical cancer patients.…”
Section: Discussionsupporting
confidence: 91%
“…The ranges of DFI and PRS in EC patients with BR were 1–148 months and 1–199 months, respectively (Table ). Patients with BR who completed initial EC treatment survived longer than those who had bone metastases at initial diagnosis . In Ucella et al and Kehoe et al ’s studies, the median survival after bone failure was 12 and 10 months, respectively .…”
Section: Discussionmentioning
confidence: 42%
“…Thus, we propose that the utilization of routine radiological work‐up in EC surveillance may increase the probability of incidental determination. Our literature review showed that the axial skeleton was most often involved in recurrent EC . Nguyen et al emphasized that BR was frequent in the appendicular skeleton when patients were at advanced surgical stage and grade, with the vertebra being the most commonly affected bone in EC patients .…”
Section: Discussionmentioning
confidence: 71%
“…Patients with multiple bone metastases were associated with poor prognosis in various kinds of malignancies [13,26,[28][29][30]; however, no previous study had specifically analyzed the prognostic value of the number of metastatic sites among patients with bone-only metastasis. It is intriguing that in our study, univariate analysis showed that both the number of metastases (multiple vs. single) and the number of metastatic sites (more than three vs. three or fewer) were associated with OS of patients with bone-only metastatic NPC; multivariate analysis including all significant covariates showed that the number of metastatic sites (more than three vs. three or fewer) but not the number of metastases (multiple vs. single) was an independent predictor for OS.…”
Section: Cmementioning
confidence: 99%